Analysis of Reward, Work Environment, Motivation and Performance of Administrative Staff - Danny Ajar Baskoro; Nadia Amelia Elyana Poluan; Rossy Pratiwy Sihombing (Lembaga Penjaminan Mutu, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study explores the impact of rewards, work environment, and motivation on the performance of administrative staff at the Faculty of Economics, State University of Malang. This study uses the Explanatory Research method with a sample of 47 employees. Data were collected through questionnaires and analysed using path analysis and SMARTPLS3 as the statistical test. The results confirmed that reward and motivation directly impact staff performance, while the work environment has no direct impact. In addition, the findings suggest that motivation serves as a mediator in the relationship between rewards, work environment, and performance. The importance of providing appropriate rewards and creating conducive working conditions to stimulate motivation has been proven in this study. These results provide a valuable perspective for educational institutions in their efforts to improve the performance of education personnel in enhancing academic services.